Knockdown of long non‐coding RNA linc‐ITGB1 inhibits cancer stemness and epithelial‐mesenchymal transition by reducing the expression of Snail in non‐small cell lung cancer. Issue 2 (28th November 2018) - Guo, Lili; Sun, Cencen; Xu, Shilei; Xu, Yue; Dong, Qiuping; Zhang, Linlin; Li, Wei; Wang, Xingyu; Ying, Guoguang; Guo, Fengjie
Abstract : Background: The main cause of death in patients with non‐small cell lung cancer (NSCLC) is the progression of cancer metastasis, which can be attributed to multiple factors, such as cancer stem cells (CSCs) and epithelial‐mesenchymal transition (EMT). Long non‐coding RNAs (lncRNAs) play important roles in the regulation of the cell cycle, cell proliferation, immune responses, and metastasis in cancers, but the potential roles and mechanisms of lincRNAs in CSC‐like properties of cancer have not yet been elucidated. Methods: Human NSCLC cell lines (A549 and H1299), highly metastatic cell lines (L9981 and 95D), and their corresponding low‐metastatic cell lines (NL9980 and 95C) were subject to quantitative real‐time PCR and Western blot, transwell invasion, colony formation, and wound healing assays. Results: Linc‐ITGB1 was greatly upregulated in CSC spheres. Linc‐ITGB1 knockdown markedly inhibited CSC formation and the expression of stemness‐associated genes, such as Sox2, Nanog, Oct‐4, c‐Myc, and CD133 . Depletion of linc‐ITGB1 expression also inhibited the in vitro invasive and migratory potential of cells, and further analysis indicated that linc‐ITGB1 knockdown increased the expression of the epithelial marker E‐cadherin and downregulated the mesenchymal markers vimentin and fibronectin. The EMT‐related transcription factor Snail mediated these effects of linc‐ITGB1 in NSCLC, and overexpression of Snail significantly reversed the inhibitory effects of linc‐ITGB1 depletion. Conclusion: Overall, our study demonstrated that linc‐ITGB1 promoted NSCLC cell EMT and cancer stemness by regulating Snail expression.